2012
DOI: 10.1111/j.1365-2605.2011.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of micropenis in 2710 male newborns from an intensive‐use pesticide area of Northeastern Brazil

Abstract: Exposure to endocrine-disrupting chemicals (EDCs) has been suggested to contribute to the increasing trends of external genital malformation in male newborns. In Northeastern Brazil, the poor sanitary conditions found in the favelas encourage the widespread use of pesticides. This 2-year study of a total birth cohort of full-term male newborns in the regional hospitals of Campina Grande (Paraíba, Brazil) sought to (1) accurately establish for the first time the incidences of neonatal male genital malformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 96 publications
0
29
0
9
Order By: Relevance
“…Além de todos esses efeitos já apresentados, os agrotóxicos podem, também, estar relacionados a alterações no binômio mãe-feto, como malformações congêni-tas 108-111 , nascimentos prematuros, índices de apgar insatisfatórios 9,112 e micropênis em recém-nascidos 113 .…”
Section: Agrotóxicos E Impactos Na Saúde Humanaunclassified
“…Além de todos esses efeitos já apresentados, os agrotóxicos podem, também, estar relacionados a alterações no binômio mãe-feto, como malformações congêni-tas 108-111 , nascimentos prematuros, índices de apgar insatisfatórios 9,112 e micropênis em recém-nascidos 113 .…”
Section: Agrotóxicos E Impactos Na Saúde Humanaunclassified
“…Similarly, estrogen exposure has been linked with higher frequency of reproductive abnormalities [15]. A high prevalence of micropenis was reported in newborns from Brazil [16] and in infants and prepubescent boys from Denmark [17] whose mothers were exposed to pesticides during pregnancy. Laboratory animals treated prenatally with estrogens developed hypospadias [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…For instance, many studies showed that contaminations of rivers with estrogenic and androgenic compounds in the ng/L range, are responsible for intersex changes within fish populations [3,4] raising concerns about population-level consequences [5]. In Brazil, a study conducted in 2710 newborn males revealed fetal contamination with organochlorine pesticides (DDT) with a risk factor for external genital malformations [6], whereas in young girls, fetal and/or environmental exposure to endocrine disrupting chemicals (EDCs) led to precocious puberty [7,8]. …”
Section: Introductionmentioning
confidence: 99%